The Normative Effect of Harmonic Loads on Pile Group Depends on the Characteristics of Dynamic Response - al rawashdeh, mohammad (European Journal of Applied Sciences, 2022)
Pile-supported machine foundations are examined in this work to identify the dynamic features of linear and nonlinear theories. A three-pile group with a 3 m pile length and an outer diameter of 0.114 m is given axial harmonic loading before field-based forcing vibration testing. For four distinct eccentric moments, tests are carried out at a static load of 12 kN. Each eccentric instant’s reaction in terms of frequency and amplitude is examined. The continuum approach technique is also used for theoretical analysis, which employs both linear and nonlinear solutions. All of the eccentric moments’ dynamic field test findings are compared to theoretically expected frequency-amplitude responses. In comparison to the actual test findings, the linear solution’s anticipated responses show lower resonant amplitudes and substantially higher resonant frequencies. The dynamic response curves predicted by the nonlinear solution fit the test findings rather well in this situation. To achieve this degree of agreement with nonlinear analysis results, precision in border zone parameters and soil-pile separation lengths was necessary.